Correlation Of The Discipline Of Church Ministers Based On Proverbs 10:17 With Church Growth In Gkb Kadosh Hammer - Fransiska Angela Sampouw; Tonny Andrian Stefanus; Maria Titik Windarti (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
Discipline is an important aspect in church ministry, especially in the leadership of pastors who serve as spiritual role models. This research explores the correlation between church ministry discipline based on Proverbs 10:17 and church growth in Kadosh Church, Palu. Using a theological approach and descriptive method, this study shows that discipline, including spiritual commitment, punctuality, and ministry management, has a significant influence on the spiritual health and growth of the congregation, both quantitatively and qualitatively. The findings of this study provide a foundation for the development of more effective ministry strategies.